MOTIVASI INDONESIA MELAKUKAN KERJASAMA IMPOR DAGING KERBAU DENGAN INDIA - Hydayat, Fikri Haddy; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study discussed the motivation of Indonesia to cooperates on the impot of buffalo meats with India. Indonesia motivation to cooperates on import of buffalo meats with India because Indonesia wants to increases its CPO’s export quota to India, because the price of CPO expected to increase in early 2017, while India itself is the largest importer of CPO in the world. Moreover, Indonesia always depending on imported meat to fulfilled its domestic needs, this situation doesn’t made the price of national meat in Indonesia more affordable to Indonesian people. Buffalo meat is relatively cheaper than cow meat, which was the most consumable meat in Indonesia, and expected to reduce the price of cow meat in Indonesia. Indonesia itself start to imported buffalo meat to Indonesia on late September 2016, where 9.500 tons of buffalo meat had arrived in IndonesiaIn discussing the problem of Indonesia motivation to cooperates on the import of buffalo meat with India, the authors use descriptive qualitative research methodology, with data collection techniques of library research (library research) derived from the sources of book literature, magazine issues, journals, and various scientific articles. The perspective used is Neoliberlism which sees the role of the state in regulating its economy. The theory used is the theory of Comparative Advantage.Keywords: Buffalo Meat, CPO, Export-Import.